Stepping Stones to Synthetic Biology - Carrà, Sergio (The Frontiers Collection,, 2018)
This book explores fascinating topics at the edge of life, guiding the reader all the way from the relation of life processes to the second law of thermodynamics and the abundance of complex organic compounds in the universe through to the latest advances in synthetic biology and metabolic engineering. The background to the book is the extraordinary scientific adventures that are being undertaken as progress is made toward the creation of an artificial cell and the control of life processes. This journey involves input from research areas as diverse as genetic engineering, physical chemistry, and information theory. Life is to be thought of not only as a chemical event but also as an information process, with the genome a repository of information gathered over time through evolution. Knowledge of the mechanisms affecting the increase in complexity associated with evolutionary paths is improving, and there appear to be analogies with the evolution of the technologies promoting the development of our society. The book will be of wide interest to students at all levels and to others with an interest in the subject.